Improvement of availability rate of overall equipment effectiveness (OEE) for CNC winding machine - Aina Nadia Aida, Mohd Latif (2015)
Most of manufacturers seek ways to reduce costs that associated with producing and distributing products. In order to reduce the cost, reduction of the losses is needed to improve the efficiency shop floor. High efficiency of machine needed to get higher p rofit in the global competition. A smooth production operation and lower downtime in production shows that the plant is in better management and maintenance. This research is proposed to eliminate waste in setting up CNC winding machine using lean techniques and subsequently improve the availability rate of OEE by reducing set up time. This research has conducted at BI Technologies Corporation production area which is at CNC winding area. By using overall equipment effectiveness as a tool, it is used to evaluate how effectively a manufacturing operation is utilized. The element of OEE which is availability, quality and performance. By propose a solution to company which is toimprove current SOP and using control chart to investigate the OEE data. Ishikawadiagram also apply to show the root cause from investigation the chart from variation. At the end, the control chart used again to indicate the improvement at CNC winding area. The improvement of downtime will lower down the losses of company, and have higher availability with degree of utilization of the resources available. This paper reports the results of this research, including the results of an industrial implementation.